Ozzy ozone Defender of Our Planet - Issue No. 3: Oozzy Goes Polar - United Nations Environment Programme (2016)
Ozzy Ozone and his friend Zoe will be falling to the North Pole and then carried around by Tilman the Polar bear. They will learn what happens to earth’s protective shield, the ozone layer, and its interlinkage with global warming. They will also meet some scientists on the Tara boat.